The Late Tang Esoteric Manual for Abhiṣeka: An Introduction, Analysis, and Translation of the Engyō Nyūdan - Wu, Yang (2021)
The Japanese manuscript Tōtōin Gishin ajari kiroku Engyō nyūdan records ritual instructions of the abhiṂeka performed by Yizhen for Engyō at Qinglongsi in 839. Both the internal logic and the social context attest to its Chinese provenance. The manuscript for the first time offers an exact performance of abhiṂeka that was actually practiced in the Chinese Buddhist saṃgha. Although the major ritual steps are drawn from different Esoteric scriptures, they are rearranged to form a new but coherent ritual rationale. The coherence of these elements in the ritual performance reflects amalgamation of the two Esoteric traditions in the late Tang. The article concludes with the first annotated English translation of the manuscript along with punctuated and critical edition of its Chinese text.
Keywords: Ritual; Esoteric Buddhism; Tang; abhiṂeka; Engyō nyūdan